The impact of mentoring and pedagogy on mitigation of library stress of undergraduate students. Issue 8 (2nd November 2017) - Alazemi, Huwayah M.; Alharbi, Awadh
Abstract : Purpose: This paper aims to justify the relevance of student-centred teaching – learning in influencing their motivation to shed library fear, source resources, attain higher-order learning, garner intellectual prowess and invent new theories. Design/methodology/approach: To assess the validity of association between guidance, pedagogy, library access and intellectual prowess, a close-ended questionnaire is used. This questionnaire was administered on 350 undergraduate students in Kuwait. The step helped to gather their responses and initiate correlation analysis. Also, correlation analysis was used to review the association between the items selected in the questionnaire, interpret outcomes and draw valid inferences. Findings: The outcome highlights that such students show keen interest to learn when faculty members give credence to educational psychology, teaching-learning quality, knowledge transfer and their transformation into knowledge seekers. The realization of such scholastic capabilities makes it possible for them to shed library fear and search disappointments, circumvent procedural complexities and pay least importance to size of library structure. Such mental state heightens their desire to use library services optimally, learn and contribute to new knowledge. Originality/value: Few attempts have been made to study the impact of mentoring and pedagogy on mitigation of library stress undergraduate students.